An overview of the plant-mediated synthesis of zinc oxide nanoparticles and their antimicrobial potential. Issue 4 (2nd April 2020) - Akbar, Sadia; Tauseef, Isfahan; Subhan, Fazli; Sultana, Nighat; Khan, Ibrar; Ahmed, Umair; Haleem, Kashif Syed
Abstract: The emergence of resistance by microorganisms to multiple antibiotics and the development of alternative strategies to control the growth of detrimental microorganisms have led to the introduction of nanoparticles as novel antimicrobial agents. Nanoparticles exhibit distinct chemical, physical and biological properties from their bulk counterparts which owe to their huge scope of applications in various areas of science and technology. Zinc oxide nanoparticles, one of the multifunctional inorganic nanoparticles, have attained ample interest for their vast applications, especially as antimicrobials. Keeping in view the potential applications of zinc oxide nanoparticles, a variety of physical and chemical approaches have been applied for their construction. Green synthesis approach employing plants have emerged as a reliable, low cost, biocompatible and eco-friendly method for the construction of zinc oxide nanoparticles. The present review provides an overview of various reports of the plant-mediated synthesis of zinc oxide nanoparticles, and their antimicrobial applications.